2007
DOI: 10.1242/jeb.006502
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual and mechanosensory cues in structuring forward flight inDrosophila melanogaster

Abstract: t has long been known that many flying insects use visual cues to orient with respect to the wind and to control their groundspeed in the face of varying wind conditions. Much less explored has been the role of mechanosensory cues in orienting insects relative to the ambient air. Here we show that Drosophila melanogaster, magnetically tethered so as to be able to rotate about their yaw axis, are able to detect and orient into a wind, as would be experienced during forward flight. Further, this behavior is velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
132
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 31 publications
14
132
0
Order By: Relevance
“…Blowflies are also known to infer rotational motion from another visual pathway that derived from the low-resolution ocelli located between their compound eyes (Parsons et al 2006). Flies also use wind to infer their own self-motion and wind modifies their responses to visual cues (Budick et al 2007). Mechanosensory cues are also important for moths when they make contact with a flower (Goyret & Raguso 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Blowflies are also known to infer rotational motion from another visual pathway that derived from the low-resolution ocelli located between their compound eyes (Parsons et al 2006). Flies also use wind to infer their own self-motion and wind modifies their responses to visual cues (Budick et al 2007). Mechanosensory cues are also important for moths when they make contact with a flower (Goyret & Raguso 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data showed that this procedure does not alter the optomotor responses of either the wings or antennae. For flies used to assess the role of the JO, we glued one antenna at the PF joint using UV-cured glue (Duro) (Budick et al, 2007) immediately after removing their prothoracic legs. Several previous studies have used this gluing procedure successfully to interfere with JO function (Budick et al, 2007;Duistermars et al, 2009;Robie et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This simulated what the fly would experience during forward flight in wind and indeed flies directed their heading towards the visually simulated upwind direction. Forward flight also requires input from mechanosensory cues, provided at least in part by the Johnston's organ (Budick et al 2007). Drosophila also orient towards vertical silhouettes, which in the flight simulator is represented by a vertical band of LEDs that are turned off; this visual stimulus presumably mimics a suitable landing or feeding site (Maimon et al 2008).…”
Section: Still-air Bioassaysmentioning
confidence: 99%